2018
DOI: 10.1111/1756-185x.13310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quality indicator monitoring for glucocorticoid‐induced osteoporosis and trends of drug treatment in a Japanese hospital

Abstract: Quality indicator monitoring for GIOP significantly improved appropriate anti-osteoporotic drug prescriptions, especially in men and postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The 50 remaining articles yielded 16 sets of indications, including 12 sets of prescribing criteria, 8 , 9 , 23 33 and 4 sets of prescribing measures. 10 , 19 , 34 , 35 Four of these 16 sets were identified by searching the references of studies employing the indications. 10 , 28 , 29 , 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 50 remaining articles yielded 16 sets of indications, including 12 sets of prescribing criteria, 8 , 9 , 23 33 and 4 sets of prescribing measures. 10 , 19 , 34 , 35 Four of these 16 sets were identified by searching the references of studies employing the indications. 10 , 28 , 29 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…Two sets were based only on guidelines. 10 , 35 One study also used patient interviews. 29 Seven sets, encompassing 421 (53.0%) prescribing indications, were developed in Europe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, a recent French study investigating whether the guidelines for prevention of GC-induced osteoporosis were applied in patients with RA found that less than 30% of those with an indication for treatment received AOD [ 46 ]. Guidelines may not be sufficient, and a Japanese group decided to increase education and attention to GC-induced osteoporosis at their hospital by introducing a quality indicator to monitor prevention and treatment of GC-induced osteoporosis [ 47 ]. They found that these interventions improved the proportion of patients treated with AOD during 2010–2013.…”
Section: Discussionmentioning
confidence: 99%